The relationships between spirituality, coping strategies, and psychological distress among haemodialysis patients - Nurul Najihah Mohamed Shukri; Abdul Rahman Ahmad Badayai (Penerbit Universiti Kebangsaan Malaysia, 2020)
Living as end-stage renal failure patients undergoing haemodialysis can be a challenge because there are restrictions in daily life. Spirituality aspects and coping strategies may play an essential role in individuals' psychological distress. Therefore, this study aims to investigate the aspect of spirituality and coping strategies with psychological distress in haemodialysis patients. Participants were 64 patients undergoing haemodialysis in Kepala Batas, Pulau Pinang. Pearson correlations and multiple regression were conducted to examine the relationship and predicting the best predictor of psychological distress. Instruments used were Daily Spiritual Experience Scale, Coping Strategies Short-Form, and Kessler-10. Results showed that there were significant correlations between spirituality aspects and psychological distress. This study also confirms that there was a significant relationship between problem-focused engagement and emotion-focused engagement with psychological distress. Likewise, emotion-focused disengagement and problem-focused disengagement also reported having a significant relationship with psychological distress. Additionally, emotion-focused disengagement was the leading cause of psychological distress among patients. Therefore, it implies that spirituality aspects and using the right coping strategies can help in managing patients' psychological distress to lead a more positive and improve everyday life.